Perbandingan Hukum Pidana Perlindungan Anak di Bawah Umur antara Indonesia dan Amerika Serikat - Biatila Elsa Duey Repali (CV WAHANA PUBLIKASI, 2024)
Children are a factor that greatly influences the growth and development of a country. Children are the hope of the nation in the future, the rights that children must obtain from their parents since the child is born into the world based on applicable laws and regulations. United Nations’ member states including Indonesia and America as countries that have signed international agreements and conventions, are responsible for complying with agreements, protocols and conventions. Child protection is an effort that aims to ensure that all children have access and rights that are fully fulfilled, so that they can live dignified and optimal lives. By providing adequate protection, we strive to create a safe, loving and supportive environment for children to grow and develop into individuals who have maximum potential. Law Number 23 of 2002 concerning Child Protection is the main foundation in child protection efforts in Indonesia. Efforts to protect children's rights and ensure their welfare are an inevitable priority. Child protection in the United States is a priority that has support from various levels of society and is regulated by a series of laws and policies that apply at the federal and state levels. Violence against children is indeed a disturbing and worrying problem, not only in Indonesia but also in Western countries such as the United States. Its rampant existence shows that violence against children knows no geographic, time or cultural boundaries. Therefore, it is important for society to unite in efforts to prevent and overcome violence against children.